Influence of growing environment on growth characters of cucumber (Cucumis sativus) - Smitha, K.; Sunil, K. M. (Journal of Tropical Agriculture, 2017)
Cucumber (Cucumis sativus) is one of the most important cucurbitaceous vegetable crops grown extensively in tropical and sub-tropical parts of India. It is considered as the fourth most important vegetable crop after tomato, cabbage and onion. A field experiment was conducted at the Agricultural Research Station, Mannuthy, Thrissur, Kerala during 2014-2015. The study was conducted in polyhouse, rain shelter and open field simultaneously in a split plot design with 3 replications with six dates of planting i.e., 15th, 25th January and 5th February 2015 and 1st, 10th and 20th of June 2015. Higher plant height (272.7cm), leaf area index (2.77) and biomass at the time of last harvest (1.4 Mg ha-1) were recorded inside the polyhouse crop compared to open field and rain shelter.